Unexpected Interruptions in the Inhaled Epoprostenol Delivery System: Incidence of Adverse Sequelae and Therapeutic Consequences in Critically Ill Patients. (14th October 2021) - Block, Jason M.; Madhok, Jai; Owyang, Clark G.; Merriman, Kristen R.; Ruoss, Stephen J.; Rao, Vidya K.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Inhaled epoprostenol is a continuously delivered selective pulmonary vasodilator that is used in patients with refractory hypoxemia, right heart failure, and postcardiac surgery pulmonary hypertension. Published data suggest that inhaled epoprostenol administration via vibrating mesh nebulizer systems may lead to unexpected interruptions in drug delivery. The frequency of these events is unknown. The objective of this study was to describe the incidence and clinical consequences of unexpected interruption in critically ill patients. DESIGN: Retrospective review and analysis. SETTING: Stanford University Hospital, a 605-bed tertiary care center. PATIENTS: Patients receiving inhaled epoprostenol in 2019. INTERVENTIONS: No interventions. MEASUREMENTS AND MAIN RESULTS: Clinical indication, duration of inhaled epoprostenol delivery, mode of respiratory support, and documented unexpected interruption. In 2019, there were 493 administrations of inhaled epoprostenol in 433 unique patients. Primary indications for inhaled epoprostenol were right heart dysfunction ( n = 394; 79.9%) and hypoxemia ( n = 92; 18.7%). Unexpected delivery interruptions occurred in 31 administrations (6.3%). Median duration of therapy prior to unexpected interruption was 2 days (interquartile range, 2–5 d). Respiratory support at the time of unexpected interruption was mechanical ventilation (61.3%), high-flow nasal cannula (35.5%), and noninvasive positive pressure ventilation (3.2%). Adverse sequelae of unexpected interruption included elevated pulmonary artery pressures ( n = 12), systemic hypotension ( n = 8), hypoxemia ( n = 8), elevated central venous pressure ( n = 4), and cardiac arrest ( n = 1). Therapeutic interventions following unexpected interruption included initiation of inhaled nitric oxide ( n = 21), increase in vasoactive medication ( n = 2), and increase in respiratory support ( n = 2). Most of the adverse events were Common Terminology Criteria for Adverse Events grade 3 and 4 (93.5%). CONCLUSIONS: A retrospective review of patients receiving inhaled epoprostenol via vibrating mesh nebulizer in 2019 revealed interruptions in 6.3% of administrations with most of these interruptions requiring therapeutic intervention. The true incidence of unexpected interruption and subsequent rate of unexpected interruption's requiring intervention is unknown due to the reliance on unexpected interruption identification and subsequent documentation in the electronic medical record. Sudden interruption in inhaled epoprostenol delivery can result in severe cardiopulmonary compromise, and on rare occasion, death.